GESTÃO PARTICIPATIVA EM UNIDADES DE CONSERVAÇÃO: O CONSELHO CONSULTIVO DA APA DO JOÃO LEITE, GOIÁS - TEIXEIRA, Kharen de Araújo (2009)
The Unit of Conservation (UCs) has been seen as an important instrument to protect biodiversity and the natural resources. However, it´s necessary to combine this protection with human presence and its need of economical, social and cultural development. The most indicated way of ensuring the envolvement and participation of the society in discussions related to the UCs is through the implementation of Management Councils. Nevertheless, it can be seen in Goiás, and in other estates of the country, the lack of efficiency of these councils, which are stuck on paper, managing to follow the rules. Out of paper, the discussed and carried out actions are still insignificant. This research aimed to make analizes of the active management efficiency through the action of management councils of Conservation Units, having the Advisory Council of the Environment Protection Area (APA) of João Leite as the subject of study. The methodology used here consisted of analising the criation and introduction process of management councils of Conservation Units in Goiás and of the existing bibliographic documents on the matter, aiming to understand its social, economical, and supporting structure, as well as the criation, introduction and management of its Council. The results show that the Council of APA of João Leite has a GOOD level of efficiency according to the pattern of efficiency test of the active management in units of conservation. The criation stage of the management council was classified as GREAT, and the implementation one as GOOD, having shown as critical aspects the patterns concerning to the items 8 (population participation); 11 (requests/discussions sent to the council); 13 (existence of management plans); 15 (administration plans usage); 18 (technical staff formation); 19 (council member condition) and 20 (communication level between the institution and society).